On the Boundedness of Quasilinear Integral Operators of Iterated Type with Oinarov’s Kernels on the Cone of Monotone Functions - Stepanov, Vladimir Dmitrievich; Shambilova, Guldarya Ermakovna (Eurasian Mathematical Journal, 2017)
We solve the characterization problem of \( L^p_v - L^r_ρ \) weighted inequalities on Lebesgue cones of monotone functions on the half-axis for quasilinear integral operators of iterated type with Oinarov’s kernels.